Peran Auditor dalam Mendeteksi dan Mencegah Kecurangan Keuangan - Hanifah Nur Andini; Aniza Listianti; Neny Pebriana; Mohammad Afrizal Miradji (Universitas Katolik Widya Karya Malang, 2024)
You may see corruption in action in today's news stories about Indonesia. Actually, there are those who see corruption as something that happens all the time and have unknowingly made it a national disease. In addition, companies that have strong internal controls might nevertheless be victims of fraud. The effects of financial fraud are far-reaching and devastating. In most cases, this causes financial report information to become inaccurate, which in turn affects top-level decision-makers. Examining how auditors may best identify and forestall instances of financial fraud is the overarching goal of this study. This research is qualitative in nature; it gathers information on social phenomena, processes and analyzes it further, and then draws conclusions. The data used for this study came from secondary sources. The findings highlight the critical and essential role of auditors in identifying different types of financial reporting fraud inside organizations.